Conductivity, Surface Tension, and Comparative Antibacterial Efficacy Study of Different Brands of Soaps of Nepal - Narendra Kumar Chaudhary; Arush Bhattarai; Biswash Guragain; Ajaya Bhattarai (Journal of Chemistry)
The current study aims to evaluate the solution properties and antibacterial efficacy study of five different brands of toilet soaps of Nepal such as Okhati (OKT), Lifebuoy (LFBY), Lux (LX), Liril (LRL), and Chiuree Neem (NM). The evaluation of critical micelle concentration (CMC) and their thermodynamics and surface properties are also reported. This study was further extended to evaluate antibacterial efficacy against three pathogenic bacteria such as Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), and Proteus vulgaris (P. vulgaris) by disc diffusion technique, and it was done at four different concentrations of soap. The bioactive ingredients present in them provide antibacterial potency to cure various skin problems caused by bacterial pathogens. Similarly, the antibacterial potency of LFBY was found higher than other soaps. Based on these studies, we can simply take LFBY soap at the highest rank in regards to antibacterial sensitivity.